Phenotypic and molecular analysis of the effect of 20-hydroxyecdysone on the human filarial parasite Brugia malayi. Issue 5 (May 2016) - Mhashilkar, Amruta S.; Adapa, Swamy R.; Jiang, Rays H.Y.; Williams, Steven A.; Zaky, Weam; Slatko, Barton E.; Luck, Ashley N.; Moorhead, Andrew R.; Unnasch, Thomas R.
Graphical abstract: Highlights: 20-hydroxyecdysone (20E) induces microfilarial release and immature abortion in Brugia malayi . 20E up-regulates 30 transcripts and 359 proteins in adult B. malayi . RNA interference (RNAi) phenotypes and their Gene Ontology (GO) terms predict involvement in embryogenic processes. Abstract: A homologue of the ecdysone receptor has been identified and shown to be responsive to 20-hydroxyecdysone in Brugia malayi . However, the role of this master regulator of insect development has not been delineated in filarial nematodes. Gravid adult female B. malayi cultured in the presence of 20-hydroxyecdysone produced significantly more microfilariae and abortive immature progeny than control worms, implicating the ecdysone receptor in regulation of embryogenesis and microfilarial development. Transcriptome analyses identified 30 genes whose expression was significantly up-regulated in 20-hydroxyecdysone-treated parasites compared with untreated controls. Of these, 18% were identified to be regulating transcription. A comparative proteomic analysis revealed 932 proteins to be present in greater amounts in extracts of 20-hydroxyecdysone-treated adult females than in extracts prepared from worms cultured in the absence of the hormone. Of the proteins exhibiting a greater than two-fold difference in the 20-hydroxyecdysone-treated versus untreated parasite extracts, 16% were involved in transcriptional regulation. RNA interference (RNAi) phenotype analysis of Caenorhabditis elegans orthologs revealed that phenotypes involved in developmental processes associated with embryogenesis were significantly over-represented in the transcripts and proteins that were up-regulated by exposure to 20-hydroxyecdysone. Taken together, the transcriptomic, proteomic and phenotypic data suggest that the filarial ecdysone receptor may play a role analogous to that in insects, where it serves as a regulator of egg development.